(untitled) (Journal of the College of Basic Education, 2022)
By means of the GR-460 mobile system, the only one in Iraq dedicated to the radiological survey process, attached to the system is a device for positioning via satellite (GPS system) so that the measurement points are linked to the spatial coordinates. The radiological surveys of the governorate were conductedThe main roads and internal streets that are easy to pass through were taken in the neighborhoods and streets of the district, and a virtual path was drawn on the map to be taken as a path for the system’s traffic. The total lengths of the paths covered by the radiological survey were about (85) km, and more than (6500) measurement points were recorded in a file. Time is one point per second.